DUKUNGAN KELUARGA, PENGETAHUAN, DAN PERSEPSI IBU SERTA HUBUNGANNYA DENGAN STRATEGI KOPING IBU PADA ANAK DENGAN GANGGUAN Autism Spectrum Disorder (ASD) - Milyawati, Lia; Hastuti, Dwi (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2009)
The objective of study was to understand family support, mother’s knowledge and perception of ASD and its association with coping strategy of mothers with ASD children. The study used a cross-sectional study design and conducted at Sekolah Khusus AL-IHSAN in Tangerang and in Cilegon, Banten. The samples of the study were 31 mothers with ASD children who were participated at AL-IHSAN and were available to be interviewed. The study conducted at February until May 2008 which included data collecting, data processing, and data analyzing. Instrumen used in the study was a modification of Coping Health Inventory for Parents (CHIP) by McCubbin and Patterson (1987). Data analyzing used was descriptive statistics, paired sample T-test, Rank-Spearman correlation, and Chi-Square. Result of the study showed that family support was considered as low (45,2%) and high or very high (54,8%). Mother’s knowledge mostly good, which classified as moderate and high (93,5%), while those classified as low was only 6,5%. In term of mother’s perception there were 45,2% mothers who still had negative perception toward ASD child. There was differences in term of coping mechanism strategy which was mostly to maintain family stability, optimism and cooperation at present, while before were mostly to seek assistance for medical treatment. The younger age of mothers and fathers, the stronger family support they received. Mother’s perception of ASD children tend to be positive when the age of ASD children is younger and the length of therapy is shorter. The characteristics of family, family support, mother’s knowledge, and perception of ASD children had no significant correlation with coping strategy used by mothers as their effort to reduce some pressures in taking care of ASD children.